Autenticação pública de documentos via Blockchain : reflexões teóricas - BARBIN, Eduardo Isper Nasif; ROLAND, Carlos Eduardo de França (109, 2020)
Desde a antiguidade a necessidade de tornar públicos atos e negócios jurídicos conviveu com o desejo do homem de organizar-se em sociedade. Estima-se que uma pessoa física utiliza os serviços de um cartório pelo menos dez vezes ao longo da vida. Ocorre que a proteção ao patrimônio jurídico das pessoas conferidos pela autenticação de documentos tornou-se um entrave, um verdadeiro gargalo à dinâmica dos modelos de negócio da vida atual além de ser um obstáculo ao exercício dos direitos das pessoas físicas em suas mais diferentes formas. A partir desta percepção foi realizada pesquisa bibliográfica exploratória para avaliar possível solução para desburocratizar os atos notariais por autenticação eletrônica de documentos através da tecnologia Blockchain. São apresentados neste artigo os fundamentos dos blockchains, seu uso em autenticação de documentos públicos, aspectos legais que regulamentam operações de certificação digital, e aspectos técnicos relacionados ao uso da tecnologia. Foram também analisadas iniciativas de adoção de blockchains por outros países a título de exemplo. Considera-se, a partir dos resultados alcançados pelos estudos bibliográficos que tal serviço poderia ser oferecido e administrado pelo Estado de forma online, gratuita e com acesso universal. A geração de novos negócios com a agilidade na consulta de documentos públicos geraria crescimento econômico com consequente aumento de arrecadação de imp

Since antiquity, the need to make legal acts and businesses public has interacted with the desire of the man to organize himself in society. It is estimated that an individual uses the services of a registry office at least ten times in his entire life. The fact is that the protection of the legal patrimony of people conferred by the authentication of documents has become an obstacle, a real barrier to the business model dynamics in today's life, in addition to being an obstacle to the exercise of the individuals’ rights in different ways. Based on this perception, some exploratory bibliographic research was carried out to assess a possible solution to reduce the bureaucracy of notarial acts by electronic document authentication through Blockchain technology. This article presents the fundamentals of blockchains, their use in public document authentication, legal aspects that regulate digital certification operations, and technical aspects related to the use of the technology. Blockchain adoption initiatives by other countries were also analyzed as an example. Based on the results achieved by bibliographical studies, it is considered that the service could be offered and administered online by the State and also free of charge and with universal access. The generation of new businesses with the agility in consulting public documents would generate economic growth with a consequent increase in tax collection, economically supporting the maintenance of the system. It is also necessary to consider the substantial savings with the reduction of bureaucracy increasing the transparency of businesses, in addition to reaching corners of Brazil that do not have the notary service
Public authentication of documents via Blockchain: theoretical reflections
Keywords: Reconhecimento de caracteres ópticos; Cartório; Documentos; Segurança de dados; Redes e comunicação de dados; Informação e Comunicação